Modelling the impact of tax structure on economic indicators / Taufik Abd Hakim - Abd Hakim, Taufik (Institute of Graduate Studies, UiTM, 2015)
This study attempts to investigate further the recent impact of tax structure on economic indicators in the different group of countries which are the low income, lower middle income, upper middle income and high income countries over the period 2000-2009 (early of modern era). Additionally, the gap between traditional schools of thought which believe that lower income tax rates generate economic growth, while modern schools of thought propagate that higher income tax rates produce economic growth especially for high income countries (Slemrod, 2003; Bonu and Pedro, 2009) motivate researcher to reveal the impact of taxes among group of countries. In this study, researcher specifies models to relate tax structure and economic indicators and estimates them using several advanced econometric approaches which are, 1) the Feasible Generalized Least Squares (FGLS), 2) Two Stage Instrumental Variables (2SIV), 3) Fixed and Random Effects Instrumental Variables (FE/ RE-IV) and, 4) Arellano-Bond Generalized Method of Moments (GMM) estimators…